Economic value of water in agriculture: comparative analysis of a water-scarce and a water-rich region in India - Kumar, M. Dinesh; Malla, A.K.; Tripathi, S.K. (2008)
The economic value of water should be markedly higher in water-scarce regions than in water-rich regions. Similarly, then the incremental return per unit of land should be higher where land is scarcer. These hypotheses are tested by comparing the situation in western Punjab, which is land-rich and naturally water-scarce and eastern Uttar Pradesh which is land-scarce and water-rich. Our regression analysis shows that every extra unit of water diverted for agriculture generates more economic surplus in western Punjab while every extra unit of land put under cultivation generates more economic surplus in eastern Uttar Pradesh. Hence, transfer of water from a water-rich, land-scarce region to a water-scarce, land-rich region for agriculture might result in the realization of higher economic value.